Famílias em tempos de crise: a regulação judicial do exercício das responsabilidades parentais - Casaleiro, Paula (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2018)
The analysis of the juvenile justice statistics points to an increase in child custody disputes. In this article it is argued that the crisis’ context and the implementation of austerity policies contribute directly and indirectly to the alteration not only of the volume, but also of the nature of the judicialized family conflicts, increasing child custody and child support disputes, namely to access social protection mechanisms.